Effects of mass models on dynamical mass estimate: the case of ultradiffuse galaxy NGC 1052-DF2. (3rd September 2018) - Hayashi, Kohei; Inoue, Shigeki
ABSTRACT: NGC 1052-DF2 was recently discovered as the dark-matter-deficient galaxy claimed by van Dokkum et al. However, large uncertainties on its dynamical mass estimate have been pointed out, concerning the paucity of sample, statistical methods, and distance measurements. In this work, we discuss the effects of the difference in modelling of the tracer profile of this galaxy on the dynamical mass estimate. To do this, we assume that the tracer densities are modelled with power-law and Sérsic profiles, and then we solve the spherical Jeans equation to estimate the dynamical mass. Applying these models to kinematic data of globular clusters in NGC 1052-DF2, we compare 90 per cent upper limits of dynamical mass-to-light ratios estimated from this analysis and from van Dokkum et al. We find that the upper limit obtained by the power-law is virtually the same as the result from van Dokkum et al, whilst this limit estimated by the Sérsic is significantly greater than that from van Dokkum et al, thereby suggesting that NGC 1052-DF2 can still be a dark-matter-dominated system. Consequently, we propose that dynamical mass estimate of a galaxy is largely affected by not only the small kinematic sample but the choice of tracer distributions, and thus the estimated mass still remains quite uncertain.